Carcinome épidermoïde sur lichen scléro-atrophique vulvaire: Epidermoid carcinoma associated with atrophic vulvar lichen sclerosus - Zemmez, Youssef (Pan Afr Med J, 2018)
We here report the case of a 58-year old female patient with no particular past medical history, presenting with a 5-year history of vulvar pruritis, drought and vulvodynia at the Department of Dermatology. Clinical examination showed diffuse porcelaine lesions at the level of the vulva, with a yellowish hemispheric nodular lesion measuring 1 cm in diameter on the whitish plates and some excoriated lesions due to scratching. A skin biopsy was performed at the level of the whitish lesions and at the level of the nodular lesion. Histological examination suggested epidermoid carcinoma for the budding lesion and atrophic vulvar lichen sclerosus for the porcelaine lesions. Surgical treatment was recommended associated with radiation therapy. This study aims to highlight the risk for atrophic vulvar lichen sclerosu degeneration.